An approximation to discrete optimal feedback controls - Jinghao Zhu; Zhiqiang Zou (International Journal of Mathematics and Mathematical Sciences)
We study discrete solutions of nonlinear optimal control problems. By value functions, we construct difference equations to approximate the optimal control on each interval of small time. We aim to find a discrete optimal feedback control. An algorithm is proposed for computing the solution of the optimal control problem.